Power Domination In Paulo Coelho’s “The Winner Stands Alone” - Vidinia Syahril (PIKTORIAL : Journal of Humanities, 2020)
The study is entitled “Power Domination In Paulo Coelho’s “The Winner Stands Alone” conducted in qualitative approach analysis of the form of power domination found between social class in “The Winner Stands Alone” novel. The goal of the study is to identify the form of power domination in social class which was described using Domination in Critical Theory’s perspective by Suka (2012). The result of this study shows that the upper class and the owner of the capital are the most dominant class. Moreover, this study shows that they have a power in the form of domination such as class domination, bureaucratic domination, technocratic domination, and cultural domination that is very influential in controlling the lower class’s activity, behaviour, and the way of thinking while they accept it unconsciously.Keyword: Power Domination, Social Class, Class Domination, Bureaucratic Domination, Technocratic Domination, Cultural Domination